Strengthening Bhinneka Tunggal Ika in Addressing Intolerance Issues in Indonesia - Langingi, Sony; Yani, Achmad; Hadja, Yeheskiel Teju (Judge : Jurnal Hukum, 2025)
Indonesia is a country with ethnic, religious, racial, and cultural diversity that is a strength in national and state life. However, in recent years, the issue of intolerance has increased, marked by discrimination against minority groups, hate speech based on SARA, and the spread of hoaxes through social media. This phenomenon has the potential to threaten national unity if not addressed with an effective strategy. Therefore, this study aims to examine the role of Bhinneka Tunggal Ika as the main principle in dealing with intolerance in Indonesia. This study uses a qualitative approach with literature study and policy analysis methods. Data were collected from various academic sources, government policies, and media studies related to the issue of intolerance. The results of the study show that strengthening the value of Bhinneka Tunggal Ika can be a strategic solution in overcoming intolerance, especially through three main aspects, namely multicultural education, strict government regulations, and the role of the media in building a positive narrative about diversity. In addition, the role of civil society, religious figures, and educational institutions are also crucial factors in maintaining social harmony. This study offers novelty by integrating various approaches in strengthening Bhinneka Tunggal Ika as the main foundation in facing the challenges of intolerance. With synergy between the government, educational institutions, media, and society, the value of diversity can continue to be maintained to strengthen national unity. The results of this study are expected to be a reference for policy makers and academics in designing more effective strategies to create a harmonious and inclusive social life in Indonesia.